Thyroid cancer in Friuli Venezia Giulia, northeastern Italy: incidence, overdiagnosis, and impact of type of surgery on survival. Issue 4 (August 2019) - Panato, Chiara; Serraino, Diego; De Santis, Emilia; Forgiarini, Ornella; Angelin, Tiziana; Bidoli, Ettore; Zanier, Loris; Del Zotto, Stefania; Vaccarella, Salvatore; Franceschi, Silvia; Dal Maso, Luigino
Background: Incidence rates of thyroid cancer (TC) increased in the last decades worldwide. This study aimed to describe TC incidence in the Friuli Venezia Giulia (FVG) region, to estimate the quota of overdiagnosis, and to investigate the impact of surgery on long-term survival after TC diagnosis. Methods: TC cases reported to the FVG population-based cancer registry during 2002–2013, aged <85 years, were included. Age standardized rates (ASR) on the European population were computed, while proportion of TC overdiagnosis was estimated in comparison with expected age-specific incidence rates from published time series. Adjusted hazard ratios of death, with 95% confidence intervals, were also estimated. Results: During 2002–2013, 1701 TC cases were reported to the FVG cancer registry, with papillary TC (78.2%) as the most frequent histologic type. ASR increased from 12.4 to 16.5 in women and from 4.3 to 6.2 in men (+33.1% and +44.2%, respectively). Overdiagnosis was estimated as 79% of TC cases in women and 64% in men. Almost all TC cases (97.1%) underwent surgery, including 84.6% of women and 78.9% of men who underwent total thyroidectomy. Up to 10 years after TC diagnosis, the type of surgery did not appear to influence survival. Conclusions: This study documented an increase in TC incidence in FVG in the last decade, with overdiagnosis accounting for a large proportion of TC diagnoses and total thyroidectomy in more than 80% of cases. These findings suggest reconsidering thyroid screening practice and aggressive therapeutic strategies, as recommended by new TC guidelines.